Toner for developing electrostatic images

JP7637823B2Active Publication Date: 2025-02-28KAO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024114782
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-07-19
Filing Date
2024-07-18
Publication Date
2025-02-28
Estimated Expiration
2044-07-18

AI Technical Summary

Benefits of technology

【0008】 本発明の静電荷像現像用トナーは、帯電安定性と加圧保存性において優れた効果を奏するものである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637823000001
    Figure 0007637823000001
  • Figure 0007637823000002
    Figure 0007637823000002
  • Figure 0007637823000003
    Figure 0007637823000003
Patent Text Reader

Abstract

To provide a toner for electrostatic charge image development which is excellent in charge stability and pressurization storage property.SOLUTION: A toner for electrostatic charge image development contains a crystalline polyester resin C and an amorphous polyester resin A, wherein the crystalline polyester resin C is a polycondensation product of an alcohol component containing 70 mol% or more of ethylene glycol and a carboxylic acid component containing an aliphatic dicarboxylic acid-based compound, the alcohol component and / or the carboxylic acid component contains a monofunctional monomer, and the amorphous polyester resin A is a polycondensation product of an alcohol component, a carboxylic acid component and polyethylene terephthalate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner for developing electrostatic images used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like. [Background technology]

[0002] Amorphous polyester resins incorporating polyethylene terephthalate and crystalline polyester resins using ethylene glycol as an alcohol component have high affinity with each other, and a toner for developing electrostatic images containing a binder resin that combines both has been proposed (see Patent Document 1).

[0003] On the other hand, polyester resins using monovalent long-chain aliphatic monomers as raw material monomers effective in reducing moisture absorption have been proposed (see Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-66536 A [Patent Document 2] Patent Publication No. 2021-189196 Summary of the Invention [Problem to be solved by the invention]

[0005] Crystalline polyester resins are used to improve the low-temperature fixability of toners, but if the dispersion state in the toner is not sufficiently controlled, the charge stability is likely to be affected. Furthermore, in recent years, in a situation where stricter heat resistance is required, it is also required to ensure pressurized storage stability at the same time.

[0006] The present invention relates to a toner for developing electrostatic images, which has excellent charge stability and storage stability under pressure. [Means for solving the problem]

[0007] The present invention relates to a toner for developing electrostatic images, which contains a crystalline polyester resin C and an amorphous polyester resin A, in which the crystalline polyester resin C is a polycondensate of an alcohol component containing 70 mol % or more of ethylene glycol and a carboxylic acid component containing an aliphatic dicarboxylic acid compound, the alcohol component and / or the carboxylic acid component containing a monofunctional monomer, and the amorphous polyester resin A is a polycondensate of the alcohol component, the carboxylic acid component, and polyethylene terephthalate. Effect of the Invention

[0008] The toner for developing electrostatic images of the present invention exhibits excellent effects in terms of charge stability and pressurized storage stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The electrostatic image developing toner of the present invention is characterized in that it contains a crystalline polyester resin (crystalline polyester resin C) using ethylene glycol and a monofunctional monomer, and an amorphous polyester resin (amorphous polyester resin A) using polyethylene terephthalate (PET). The reason why the electrostatic image developing toner of the present invention has excellent charge stability and pressurized storage stability is not clear, but is presumed to be as follows.

[0010] In a crystalline polyester resin that contains ethylene glycol as the main alcohol component and further contains a component derived from a monofunctional monomer, the component derived from the monofunctional monomer forms the terminal structure of the resin and is more hydrophobic than the terminals of carboxyl groups or hydroxyl groups. On the other hand, in the case of amorphous polyester resin obtained using PET, the PET undergoes depolymerization during the polycondensation reaction between the alcohol component, the carboxylic acid component, and PET, and is incorporated into the polyester resin chain through an ester exchange reaction, but is not completely randomized and exists in the resin as a unit of a certain length that can be called a PET segment. Since the affinity between this PET segment and the crystalline polyester resin, which has ethylene glycol as the main component of the alcohol component, is high, the dispersibility of the crystalline polyester resin in the amorphous polyester resin is improved and crystallization is promoted. As a result, the toner exhibits good storage stability even when stored under pressure, and the hydrophobic end derived from the monofunctional monomer is oriented toward the outside from the domain of the crystalline polyester resin with improved dispersibility present near the surface of the toner particle, which is thought to reduce the hygroscopicity of the toner and provide excellent charging stability.

[0011] The crystalline polyester resin C is a polycondensation product of an alcohol component containing ethylene glycol as a main component and a carboxylic acid component containing an aliphatic dicarboxylic acid compound.

[0012] The content of ethylene glycol in the alcohol component is 70 mol% or more, preferably 80 mol% or more, more preferably 90 mol% or more, even more preferably 95 mol% or more, and 100 mol% or less. When the alcohol component contains a monoalcohol, the content is preferably 98 mol% or less, more preferably 95 mol% or less.

[0013] Examples of other alcohol components include aliphatic diols other than ethylene glycol, such as 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, neopentyl glycol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol; alkylene oxide adducts of bisphenol A; aromatic diols such as bisphenol A; hydrogenated bisphenol A; sorbitol, pentaerythritol, glycerin, and trimethylolpropane; and other trihydric or higher alcohols.

[0014] Examples of the aliphatic dicarboxylic acid compound include succinic acid (carbon number: 4), fumaric acid (carbon number: 4), adipic acid (carbon number: 6), suberic acid (carbon number: 8), azelaic acid (carbon number: 9), sebacic acid (carbon number: 10), dodecanedioic acid (carbon number: 12), tetradecanedioic acid (carbon number: 14), succinic acid having an alkyl group or an alkenyl group on the side chain, anhydrides of these acids, and alkyl esters of these acids having a carbon number of 1 to 3. Here, when the aliphatic dicarboxylic acid compound is an alkyl ester, the carbon number of the alkyl group is not included in the above carbon number.

[0015] From the viewpoint of hydrophobicity, the carbon number of the aliphatic dicarboxylic acid compound is preferably 4 or more, more preferably 8 or more, even more preferably 10 or more, and still more preferably 12 or more, and from the viewpoint of low-temperature fixability, the carbon number is preferably 16 or less, more preferably 14 or less.

[0016] The aliphatic dicarboxylic acid compound may be either a saturated aliphatic dicarboxylic acid compound or an unsaturated aliphatic dicarboxylic acid compound, but from the viewpoint of storage stability under pressure, it is preferably a saturated aliphatic dicarboxylic acid compound.

[0017] From the viewpoint of pressurized storage stability, the content of the aliphatic dicarboxylic acid compound in the carboxylic acid component is preferably 80 mol% or more, more preferably 90 mol% or more, even more preferably 95 mol% or more, and 100 mol% or less. When the carboxylic acid component contains a monocarboxylic acid compound, the content is preferably 98 mol% or less, more preferably 95 mol% or less.

[0018] Examples of other carboxylic acid components include aromatic dicarboxylic acid compounds such as phthalic acid, isophthalic acid, and terephthalic acid, and trivalent or higher carboxylic acid compounds such as trimellitic acid and pyromellitic acid.

[0019] Furthermore, the alcohol component and / or the carboxylic acid component of the crystalline polyester resin C contains a monofunctional monomer.

[0020] Examples of monofunctional monomers contained in the alcohol component include aliphatic monoalcohols such as capryl alcohol, capric alcohol, lauryl alcohol, myristyl alcohol, palmityl alcohol, stearyl alcohol, and behenyl alcohol.

[0021] Examples of monofunctional monomers contained in the carboxylic acid component include aliphatic monocarboxylic acids such as caproic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, and behenic acid, and aliphatic monocarboxylic acid compounds such as alkyl esters of these acids in which the alkyl group has 1 to 3 carbon atoms.

[0022] From the viewpoint of improving hydrophobicity, the monofunctional monomer preferably contains an aliphatic monocarboxylic acid compound and / or an aliphatic monoalcohol.

[0023] From the viewpoint of hydrophobicity, the carbon number of the aliphatic monoalcohol is preferably 6 or more, more preferably 9 or more, even more preferably 10 or more, and even more preferably 12 or more, and from the viewpoint of low-temperature fixability, the carbon number is preferably 24 or less, more preferably 23 or less, and even more preferably 22 or less.

[0024] From the viewpoint of hydrophobicity, the carbon number of the aliphatic monocarboxylic acid compound is preferably 6 or more, more preferably 9 or more, and even more preferably 10 or more, and from the viewpoint of low-temperature fixability, it is preferably 24 or less, more preferably 23 or less, and even more preferably 22 or less. Here, when the aliphatic monocarboxylic acid compound is an alkyl ester, the carbon number of the alkyl group is not included in the above carbon number.

[0025] The content of the monofunctional monomer in the total amount of the alcohol component and the carboxylic acid component is preferably 2 mol % or more, more preferably 3 mol % or more, and even more preferably 5 mol % or more, and from the viewpoint of pressurized storage stability, it is preferably 30 mol % or less, more preferably 25 mol % or less, and even more preferably 20 mol % or less.

[0026] In this specification, macromonomers and hydroxycarboxylic acids are not included in the alcohol component and the carboxylic acid component.

[0027] The equivalent ratio of the carboxy group of the carboxylic acid component to the hydroxyl group of the alcohol component (COOH group / OH group) is preferably 0.8 or more, more preferably 0.9 or more, from the viewpoint of pressurized storage stability, and is preferably 1.2 or less, more preferably 1.1 or less, from the viewpoint of low-temperature fixability.

[0028] The crystalline polyester resin C can be produced, for example, by polycondensing an alcohol component and a carboxylic acid component in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and further, if necessary, in the presence of a co-catalyst, a polymerization inhibitor, etc., at a temperature preferably of 120°C or higher and 230°C or lower.

[0029] Examples of the esterification catalyst include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, and titanium compounds such as titanium diisopropoxybis(triethanolaminate) and titanium dihydroxybis(triethanolaminate). The amount of the esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 1.5 parts by mass or less, more preferably 1 part by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the co-catalyst for the esterification catalyst include gallic acid. The amount of the co-catalyst used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the polymerization inhibitor include tert-butylcatechol. The amount of the polymerization inhibitor used is preferably 0.001 part by mass or more, more preferably 0.01 part by mass or more, and preferably 0.5 part by mass or less, more preferably 0.1 part by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.

[0030] In the present invention, the polyester resin may be modified to such an extent that its properties are not substantially impaired. Examples of modified polyester resins include polyester resins grafted or blocked with phenol, urethane, epoxy, or the like by the methods described in JP-A-11-133668, JP-A-10-239903, JP-A-8-20636, etc., and among the modified polyester resins, urethane-modified polyester resins in which polyester resins are urethane-extended with a polyisocyanate compound are preferred.

[0031] The softening point of the crystalline polyester resin C is preferably 50°C or higher, more preferably 65°C or higher, and even more preferably 70°C or higher from the viewpoint of pressurized storage stability, and is preferably 120°C or lower, and more preferably 110°C or lower from the viewpoint of low-temperature fixability.

[0032] The crystallinity of a resin is represented by a crystallinity index defined as the ratio of the softening point to the maximum endothermic peak temperature measured by a differential scanning calorimeter, that is, the value of [softening point / maximum endothermic peak temperature]. The crystalline resin is a resin having a crystallinity index of 0.6 or more, preferably 0.7 or more, more preferably 0.9 or more, and 1.4 or less, preferably 1.2 or less, more preferably 1.1 or less. On the other hand, an amorphous resin is a resin in which no endothermic peak is observed, or if an endothermic peak is observed, the resin has a crystallinity index of more than 1.4, preferably more than 1.5, more preferably 1.6 or more, or less than 0.6, preferably 0.5 or less. The crystallinity of the resin can be adjusted by the type and ratio of the raw material monomers, and the production conditions (e.g., reaction temperature, reaction time, cooling rate), etc. The maximum endothermic peak temperature refers to the temperature of the peak with the largest peak area among the observed endothermic peaks. In the case of a crystalline resin, the maximum endothermic peak temperature is the melting point.

[0033] The melting point of the crystalline polyester resin C is preferably 60° C. or higher, more preferably 70° C. or higher, from the viewpoint of pressurized storage stability, and is preferably 130° C. or lower, more preferably 120° C. or lower, from the viewpoint of low-temperature fixability.

[0034] The acid value of the crystalline polyester resin C is preferably 1 mgKOH / g or more, more preferably 3 mgKOH / g or more, from the viewpoint of electrostatic charge stability, and is preferably 20 mgKOH / g or less, more preferably 15 mgKOH / g or less, from the viewpoint of pressurized storage stability.

[0035] The content of crystalline polyester resin C in the total amount of crystalline polyester resin C and amorphous polyester resin A is preferably 3 mass% or more, more preferably 5 mass% or more, and even more preferably 8 mass% or more, from the viewpoint of low-temperature fixability and pressurized storage stability, and is preferably 30 mass% or less, more preferably 25 mass% or less, and even more preferably 20 mass% or less, from the viewpoint of pressurized storage stability.

[0036] The amorphous polyester resin A is a polycondensation product of an alcohol component, a carboxylic acid component, and PET.

[0037] From the viewpoints of pressurized storage stability and electrostatic charge stability, the alcohol component preferably contains an aliphatic diol having 3 or more and 6 or less carbon atoms.

[0038] Examples of the aliphatic diol having 3 to 6 carbon atoms include 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, etc. Among these, neopentyl glycol is preferred from the viewpoint of pressurized storage stability.

[0039] From the viewpoint of pressurized storage stability, the content of the aliphatic diol having 3 to 6 carbon atoms in the alcohol component is preferably 30 mol % or more, more preferably 40 mol % or more, even more preferably 50 mol % or more, and 100 mol % or less, and when the alcohol component contains a trihydric or higher alcohol, it is preferably 98 mol % or less, more preferably 90 mol % or less. However, the alcohol component here does not include the ethylene glycol unit of PET.

[0040] Examples of other alcohol components include aliphatic diols having 7 or more carbon atoms, alkylene oxide adducts of bisphenol A, aromatic diols such as bisphenol A, hydrogenated bisphenol A, sorbitol, pentaerythritol, glycerin, trimethylolpropane, and other trihydric or higher alcohols.

[0041] From the viewpoint of charging stability, the carboxylic acid component preferably contains an aromatic dicarboxylic acid compound.

[0042] Examples of the aromatic dicarboxylic acid compound include phthalic acid, isophthalic acid, terephthalic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.

[0043] The content of the aromatic dicarboxylic acid compound in the carboxylic acid component is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and still more preferably 95 mol% or more, and 100 mol% or less, and when the carboxylic acid component contains a trivalent or higher carboxylic acid compound, it is preferably 98 mol% or less, more preferably 90 mol% or less, provided that the carboxylic acid component does not include the terephthalic acid unit contained in PET.

[0044] Examples of carboxylic acid components other than aromatic dicarboxylic acid compounds include fumaric acid, maleic acid, succinic acid, succinic acid derivatives substituted with a hydrocarbon group, aliphatic dicarboxylic acids such as glutaric acid, adipic acid, and sebacic acid, trivalent or higher carboxylic acids such as trimellitic acid and pyromellitic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.

[0045] In order to adjust the softening point, trivalent or higher raw monomers may be used for the alcohol component and / or carboxylic acid component of the amorphous polyester resin A. In this case, trivalent or higher alcohols, preferably glycerin or trimethylolpropane, more preferably glycerin, are preferably used in terms of charge stability. The content of the trivalent or higher raw monomers is preferably 2 mol% or more, more preferably 4 mol% or more, and preferably 25 mol% or less, more preferably 20 mol% or less, based on the total amount of the alcohol component, the carboxylic acid component, and the PET.

[0046] The alcohol component may appropriately contain a monohydric alcohol, and the carboxylic acid component may appropriately contain a monovalent carboxylic acid compound.

[0047] PET is produced by polycondensation of alcohol and carboxylic acid, and / or by depolymerization of a portion of PET. The ethylene glycol and terephthalic acid are used as raw monomers in the polycondensation reaction and are incorporated into polyester resin. PET is an equimolar polycondensation product of ethylene glycol and terephthalic acid, and the ethylene glycol and terephthalic acid that make up PET are regarded as the alcohol and carboxylic acid components, respectively.

[0048] The PET may be new virgin PET or recycled PET. Recycled PET is made by collecting used PET, washing it as necessary, and separating it from other materials before crushing it. The crushed material is then depolymerized to break it down into monomer units, which are then used to resynthesize the material.

[0049] In the present invention, the PET is preferably a PET having a relatively low IV value, i.e., a low molecular weight, compared to conventionally used PET. By introducing a PET having a low IV value (low molecular weight) into the polyester resin, the depolymerization of the PET proceeds more uniformly.

[0050] From the above viewpoints, the IV value of PET is preferably 0.40 or more, more preferably 0.45 or more, even more preferably 0.50 or more, and even more preferably 0.55 or more, and from the viewpoints of low-temperature fixability and uniformity of depolymerization, it is preferably 0.85 or less, more preferably 0.80 or less, even more preferably 0.75 or less, even more preferably 0.70 or less, and even more preferably 0.65 or less. The IV value is an intrinsic viscosity and is an index of molecular weight. The IV value of PET can be adjusted by the polycondensation time, etc.

[0051] Commercially available PET products with an IV value of 0.40 or more and 0.85 or less include RAMAPET L1 (manufactured by Indorama Ventures, IV value: 0.60), RAMAPET BF3067 (manufactured by Indorama Ventures, IV value: 0.65), RAMAPET N2G (manufactured by Indorama Ventures, IV value: 0.75), TRN-NTJ (manufactured by Teijin Limited, IV value: 0.53), TRN-RTJC (manufactured by Teijin Limited, IV value: 0.64), RAMAPET S1 (manufactured by Indorama Ventures, IV value: 0.84), and UK-31 (manufactured by Utsumi Recycle Systems Co., Ltd., IV value: 0.67).

[0052] The content of the low IV PET in the total amount of PET used in polycondensation is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 98% by mass or more, and still more preferably 100% by mass.

[0053] The PET content is preferably 5 mol% or more, more preferably 10 mol% or more, even more preferably 15 mol% or more, even more preferably 20 mol% or more, and is preferably 75 mol% or less, more preferably 70 mol% or less, even more preferably 65 mol% or less, in terms of pressurized storage stability, based on the total amount of the alcohol component, the carboxylic acid component, and the PET. When the amorphous polyester resin A is composed of two or more resins, the weighted average of the PET contents of the respective resins is taken as the PET content of the amorphous polyester resin A. In addition, since PET is a polycondensation product of ethylene glycol and terephthalic acid, dimethyl terephthalate, etc., the terephthalic acid-ethylene glycol unit (Mw: 192) is calculated as 1 mole. Therefore, the number of moles of PET = the number of moles of ethylene glycol units = the number of moles of terephthalic acid units.

[0054] The equivalent ratio (COOH group / OH group) of the carboxylic acid component (including the terephthalic acid unit in the PET) to the alcohol component (including the ethylene glycol unit in the PET) is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.

[0055] The polycondensation reaction conditions of the alcohol component, the carboxylic acid component, and the PET of the amorphous polyester resin are similar to those of the crystalline polyester resin, except that the suitable reaction temperature is preferably 130°C or more, more preferably 170°C or more, and preferably 250°C or less, more preferably 240°C or less.

[0056] The softening point of the amorphous polyester resin A is preferably 70°C or higher, more preferably 90°C or higher, and even more preferably 100°C or higher from the viewpoint of charging stability, and is preferably 170°C or lower, more preferably 160°C or lower, and even more preferably 150°C or lower from the viewpoint of low-temperature fixability.

[0057] From the viewpoints of low-temperature fixability and fixing width, the amorphous polyester resin A may be composed of resins having different softening points. The difference in softening point between the two resins is preferably 10° C. or more, more preferably 20° C. or more, and is preferably 60° C. or less, more preferably 40° C. or less.

[0058] The softening point of the amorphous resin having the higher softening point (resin AH) is preferably 100°C or higher, more preferably 110°C or higher, and even more preferably 120°C or higher, from the viewpoint of fixing width, and is preferably 170°C or lower, more preferably 160°C or lower, and even more preferably 150°C or lower, from the viewpoint of low-temperature fixing ability.

[0059] Furthermore, the softening point of the amorphous resin having the lower softening point (resin AL) is preferably 70°C or higher, more preferably 90°C or higher, and even more preferably 100°C or higher, from the viewpoint of charging stability, and is preferably 130°C or lower, more preferably 125°C or lower, and even more preferably 120°C or lower, from the viewpoint of low-temperature fixing ability.

[0060] The mass ratio of resin AH to resin AL (resin AH / resin AL) is preferably 10 / 90 or more, more preferably 20 / 80 or more, even more preferably 30 / 70 or more, and is preferably 90 / 10 or less, more preferably 80 / 20 or less, even more preferably 75 / 25 or less.

[0061] The glass transition temperature of the amorphous polyester resin A is preferably 40° C. or higher, more preferably 50° C. or higher, from the viewpoint of pressurized storage stability, and is preferably 80° C. or lower, more preferably 70° C. or lower, from the viewpoint of electrostatic charge stability.

[0062] The acid value of the amorphous polyester resin A is preferably 1 mgKOH / g or more, more preferably 3 mgKOH / g or more, from the viewpoint of electrostatic charge stability, and is preferably 20 mgKOH / g or less, more preferably 18 mgKOH / g or less, from the viewpoint of pressurized storage stability.

[0063] The content of amorphous polyester resin A in the total amount of crystalline polyester resin C and amorphous polyester resin A is, from the viewpoints of electrostatic charge stability and pressurized storage stability, preferably 70 mass % or more, more preferably 75 mass % or more, even more preferably 80 mass % or more, and is preferably 97 mass % or less, more preferably 95 mass % or less, even more preferably 92 mass % or less.

[0064] From the viewpoints of electrostatic charge stability and pressurized storage stability, the mass ratio of crystalline polyester resin C to amorphous polyester resin A (crystalline polyester resin C / amorphous polyester resin A) is preferably 3 / 97 or more, more preferably 5 / 95 or more, even more preferably 8 / 92 or more, and is preferably 30 / 70 or less, more preferably 25 / 75 or less, even more preferably 20 / 80 or less.

[0065] In the toner, the crystalline polyester resin C and the amorphous polyester resin A are contained as binder resins.

[0066] Other examples of the binder resin include vinyl resins such as styrene-acrylic resin, epoxy resin, polycarbonate, polyurethane, and composite resins containing two or more of these resins.

[0067] The total content of the crystalline polyester resin C and the amorphous polyester resin A in the binder resin is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 100% by mass.

[0068] In addition, the content of the binder resin in the toner is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and is preferably less than 100% by mass, more preferably 98% by mass or less, even more preferably 95% by mass or less.

[0069] The toner for developing electrostatic images of the present invention may contain additives such as a colorant, a release agent, a charge control agent, a magnetic powder, a flowability improver, a conductivity adjuster, a reinforcing filler such as a fibrous substance, an antioxidant, and a cleaning property improver, in addition to the binder resin.

[0070] As the colorant, dyes, pigments, magnetic materials, etc. used as colorants for toners can be used. For example, carbon black, phthalocyanine blue, permanent brown FG, brilliant fast scarlet, pigment red 122, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, isoindoline, disazo yellow, etc. can be mentioned. In the present invention, the toner may be either a black toner or a color toner.

[0071] From the viewpoint of improving the image density and low-temperature fixability of the toner, the content of the colorant is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0072] Examples of the release agent include hydrocarbon waxes such as polypropylene wax, polyethylene wax, ethylene propylene copolymer wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, and oxides thereof; ester waxes such as carnauba wax, montan wax, and deacidified waxes thereof, and fatty acid ester wax; fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts. These may be used alone or in combination of two or more.

[0073] The melting point of the release agent is preferably 60° C. or higher, more preferably 70° C. or higher, from the viewpoint of pressurized storage stability of the toner, and is preferably 160° C. or lower, more preferably 140° C. or lower, even more preferably 120° C. or lower, and even more preferably 110° C. or lower, from the viewpoint of low-temperature fixability.

[0074] The content of the release agent is, from the viewpoints of the charge stability and pressurized storage stability of the toner and dispersibility in the binder resin, preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 1.5 parts by mass or more, relative to 100 parts by mass of the binder resin, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 7 parts by mass or less.

[0075] The charge control agent is not particularly limited, and may contain either a positively chargeable charge control agent or a negatively chargeable charge control agent.

[0076] Examples of the positively charged charge control agent include nigrosine dyes such as "Nigrosine Base EX", "Oil Black BS", "Oil Black SO", "Bontron N-01", "Bontron N-04", "Bontron N-07", "Bontron N-09", and "Bontron N-11" (all manufactured by Orient Chemical Industries Co., Ltd.); triphenylmethane dyes containing a tertiary amine as a side chain; quaternary ammonium salt compounds such as "Bontron P-51" (manufactured by Orient Chemical Industries Co., Ltd.), cetyltrimethylammonium bromide, and "COPY CHARGE PX Examples of such resins include "VP435" (manufactured by Clariant), etc.; polyamine resins, such as "AFP-B" (manufactured by Orient Chemical Industry Co., Ltd.); imidazole derivatives, such as "PLZ-2001" and "PLZ-8001" (both manufactured by Shikoku Kasei Corporation); and styrene-acrylic resins, such as "FCA-701PT" and "FCA-201-PS" (manufactured by Fujikura Kasei Co., Ltd.).

[0077] Examples of the negatively chargeable charge control agent include metal-containing azo dyes such as "Varifast Black 3804", "Bontron S-31", "Bontron S-32", "Bontron S-34", and "Bontron S-36" (all manufactured by Orient Chemical Industry Co., Ltd.), "Aizenspiron Black TRH", and "T-77" (manufactured by Hodogaya Chemical Industry Co., Ltd.); metal compounds of benzilic acid compounds such as "LR-147" and "LR-297" (all manufactured by Nippon Carlit Co., Ltd.); metal compounds of salicylic acid compounds such as "Bontron E-81", "Bontron E-84", "Bontron E-88", and "Bontron E-304" (all manufactured by Orient Chemical Industry Co., Ltd.), and "TN-105" (manufactured by Hodogaya Chemical Industry Co., Ltd.); copper phthalocyanine dyes; and quaternary ammonium salts such as "COPY CHARGE NX VP434 (Clariant), nitroimidazole derivatives, and organometallic compounds.

[0078] From the viewpoint of the charging stability of the toner, the content of the charge control agent is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0079] The toner may be a toner obtained by any conventionally known method such as a melt kneading method, an emulsion aggregation method, or a suspension polymerization method, and may also be a toner having a core-shell structure, but from the viewpoint of charge stability, a pulverized toner by a melt kneading method is preferred. In the case of a pulverized toner by a melt kneading method, for example, a binder resin containing a crystalline polyester resin C and an amorphous polyester resin A, and raw materials such as a colorant, a release agent, and a charge control agent, if necessary, are uniformly mixed in a mixer such as a Henschel mixer, and then melt kneaded in an internal kneader, a single-screw or twin-screw extruder, an open roll type kneader, or the like, and cooled, pulverized, and classified to produce the toner.

[0080] In the toner of the present invention, it is preferable to use an external additive in order to improve transferability. Examples of the external additive include inorganic fine particles such as silica, alumina, titania, zirconia, tin oxide, and zinc oxide, and organic fine particles such as melamine resin fine particles and polytetrafluoroethylene resin fine particles, and two or more of them may be used in combination. Among these, silica is preferable, and from the viewpoint of transferability of the toner, hydrophobic silica that has been hydrophobized is more preferable.

[0081] Examples of hydrophobic treatment agents for hydrophobizing the surface of silica particles include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), cyclic silazane, silicone oil, aminosilane, octyltriethoxysilane (OTES), and methyltriethoxysilane.

[0082] From the viewpoints of the chargeability, fluidity, and transferability of the toner, the average particle size of the external additive is preferably 5 nm or more, more preferably 10 nm or more, and even more preferably 15 nm or more, and is preferably 250 nm or less, more preferably 200 nm or less, and even more preferably 90 nm or less.

[0083] The external addition treatment by mixing the toner particles with the external additives can be carried out according to a conventional method, and a mixer such as a Henschel mixer can be used.

[0084] From the viewpoint of the electrostatic chargeability, fluidity, and transferability of the toner, the content of the external additive is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the toner particles before being treated with the external additive, and is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less.

[0085] The volume median particle size (D 50 ) is preferably 3 μm or more, more preferably 4 μm or more, and is preferably 15 μm or less, more preferably 10 μm or less. 50) refers to the particle size at which the cumulative volume frequency calculated by volume fraction is 50% calculated from the smallest particle size. In addition, when the toner is treated with an external additive, the volume median particle size of the toner particles before treatment with the external additive is regarded as the volume median particle size of the toner.

[0086] The toner of the present invention can be used as it is as a toner for one-component development, or as a toner for two-component development mixed with a carrier, in an image forming apparatus of a one-component development system or a two-component development system, respectively. EXAMPLES

[0087] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Physical properties of resins and the like can be measured by the following methods.

[0088] [PET IV value] The viscosity is calculated from the following formula: Dissolve the solution at a concentration of 4 g / L in a mixed solvent of phenol / tetrachloroethane at a mass ratio of 60 / 40, measure using an Ubbelohde viscometer, and IV=(-1+√(1+4kη)) / (2kC) [Where k = 0.33, C = 0.004 g / mL, and η = (t 1 / t 0 )-1(t 0 : Time required for the solvent to fall, t 1 : the number of seconds it takes for the sample solution to fall.

[0089] [Softening point of resin] Using a flow tester "CFT-500D" (Shimadzu Corporation), 1g of sample is heated at a temperature increase rate of 6℃ / min while applying a load of 1.96MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1mm and a length of 1mm. The amount of plunger descent of the flow tester is plotted against the temperature, and the temperature at which half of the sample has flowed out is taken as the softening point.

[0090] [Maximum endothermic peak temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan, Inc.), weigh 0.01 to 0.02 g of sample into an aluminum pan, cool from room temperature (25°C) to 0°C at a rate of 10°C / min, and maintain at 0°C for 1 minute. Then, measure at a rate of 10°C / min. The temperature of the peak with the largest peak area among the observed endothermic peaks is regarded as the maximum endothermic peak temperature. For crystalline resins, the maximum endothermic peak temperature is regarded as the melting point.

[0091] [Glass transition temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample is weighed into an aluminum pan, heated to 200°C, and cooled from that temperature to 0°C at a rate of 10°C / min. The sample is then heated at a rate of 10°C / min and the endothermic peak is measured. The glass transition temperature is the temperature at the intersection of the extension of the baseline below the maximum endothermic peak temperature and the tangent line showing the maximum slope from the rising part of the peak to the top of the peak.

[0092] [Acid value of resin] Measurements are performed based on the method of JIS K 0070:1992, except that the measurement solvent is changed from the ethanol and ether mixture specified in JIS K 0070 to a mixture of acetone and toluene (acetone:toluene = 1:1 (volume ratio)) for amorphous resins, and to a mixture of chloroform and dimethylformamide (chloroform:dimethylformamide = 7:3 (volume ratio)) for crystalline resins.

[0093] [Melting point of release agent] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of sample is weighed into an aluminum pan, heated to 200°C, and then cooled from 200°C to 0°C at a rate of 10°C / min. The sample is then heated at a rate of 10°C / min, the amount of heat is measured, and the maximum endothermic peak temperature is taken as the melting point.

[0094] [Volume Median Particle Size and CV Value of Resin Particles, Colorant Particles, and Release Agent Particles] (1) Measuring device: Laser diffraction type particle size measuring device "LA-920" (manufactured by Horiba, Ltd.) (2) Measurement conditions: Put the sample dispersion in a measurement cell, add distilled water, and measure the volume median particle size (D 50 ) and the volume average particle size are measured. The CV value is calculated according to the following formula. CV value (%) = (Standard deviation of particle size distribution / Volume average particle size) x 100

[0095] [Solid Content Concentration of Resin Dispersion, Colorant Dispersion, and Release Agent Dispersion] Using an infrared moisture meter "FD-230" (Kett Electric Laboratory Co., Ltd.), 5 g of the measurement sample is dried at a drying temperature of 150°C and measurement mode 96 (monitoring time 2.5 minutes, fluctuation range 0.05%), and the moisture content (mass%) of the dispersion is measured. The solid content concentration is calculated according to the following formula. Solid concentration (mass%) = 100-moisture (mass%)

[0096] [Volume Median Particle Size of Agglomerated Particles] Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured and the volume median particle size (D 50 ) is required.

[0097] [Average particle size of external additives] The average particle size refers to the number-average particle size, and is calculated by measuring the particle sizes (average of major and minor diameters) of 500 particles in a scanning electron microscope (SEM) photograph and averaging these by number.

[0098] [Volume median particle size of toner (D50 )〕 Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Dispersion liquid: Polyoxyethylene lauryl ether "Emulgen (registered trademark) 109P" (manufactured by Kao Corporation, HLB (Griffin) = 13.6) was dissolved in the electrolyte to adjust the concentration to 5% by mass. Dispersion conditions: 10 mg of the measurement sample is added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser (machine name: US-1, manufactured by SND Co., Ltd., output: 80 W). Then, 25 mL of electrolyte is added, and the mixture is further dispersed for 1 minute using the ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion was added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles could be measured in 20 seconds. Then, 30,000 particles were measured, and the volume median particle size (D 50 ) is required.

[0099] [Circularity of Toner] The circularity of the toner particles is measured under the following conditions. Measurement equipment: Flow-type particle image analyzer "FPIA-3000" (Sysmex Corporation) Preparation of dispersion: A dispersion of toner particles is prepared by diluting it with deionized water so that the solid content concentration becomes 0.001 to 0.05% by mass. Measurement mode: HPF measurement mode

[0100] Resin manufacturing example 1 The alcohol component, carboxylic acid component, PET, esterification catalyst, and cocatalyst shown in Tables 1 to 6 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer, and a thermocouple, and the mixture was held at 180°C for 1 hour under a nitrogen atmosphere, then heated from 180°C to 235°C at a rate of 10°C / h, and polycondensed at 235°C for 5 hours. The temperature was then lowered to 210°C, and the reaction was continued under a reduced pressure of 10 kPa until the softening points shown in Tables 1 to 6 were reached, to obtain amorphous polyester resins (resins AH1 to AH7, AH12, AH13, resins AL1 to AL6, AL11, AL12). The physical properties are shown in Tables 1 to 6.

[0101] Resin manufacturing example 2 The alcohol component, carboxylic acid component other than trimellitic anhydride, PET, esterification catalyst, and cocatalyst shown in Tables 2 and 3 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer, and a thermocouple, and the temperature was raised to 235°C under a nitrogen atmosphere, and polycondensation was carried out at 235°C for 6 hours. The temperature was then lowered to 210°C, and trimellitic anhydride shown in Tables 2 and 3 was added, and the reaction was carried out at 210°C for 1 hour, and then the reaction was further carried out at 210°C under a reduced pressure of 10 kPa until the softening point shown in Tables 2 and 3 was reached, to obtain amorphous polyester resins (resins AH8, AH11, and AH14). The physical properties are shown in Tables 2 and 3.

[0102] Resin manufacturing example 3 The alcohol component, carboxylic acid component, esterification catalyst, and cocatalyst shown in Tables 2 and 5 were placed in a 5-liter four-neck flask equipped with a nitrogen inlet tube, a dehydration tube equipped with a fractionating tube through which hot water of 98°C was passed, a stirrer, and a thermocouple, and the mixture was kept at 180°C for 1 hour under a nitrogen atmosphere, and then heated from 180°C to 235°C at a rate of 10°C / h, and polycondensed at 235°C for 5 hours. The temperature was then lowered to 210°C, and the reaction was continued at 210°C under a reduced pressure of 10 kPa until the softening point shown in Tables 2 and 5 was reached, to obtain amorphous polyester resins (resins AH9 to AH10, AL8 to AL9). The physical properties are shown in Tables 2 and 5.

[0103] Resin manufacturing example 4 The alcohol component, carboxylic acid component, PET, esterification catalyst, and cocatalyst shown in Tables 5 and 6 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer, and a thermocouple, and the temperature was raised to 235°C under a nitrogen atmosphere, and polycondensation was carried out at 235°C for 6 hours. The temperature was then lowered to 210°C, and the reaction was carried out under a reduced pressure of 10 kPa until the softening points shown in Tables 5 and 6 were reached, to obtain amorphous polyester resins (resins AL7, AL10, and AL13). The physical properties are shown in Tables 5 and 6.

[0104] [Table 1]

[0105] [Table 2]

[0106] [Table 3]

[0107] [Table 4]

[0108] [Table 5]

[0109] [Table 6]

[0110] Resin manufacturing example 5 The alcohol and carboxylic acid components shown in Tables 7 and 8 were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the temperature was raised to 200°C over 8 hours in a nitrogen atmosphere in a mantle heater. Then, an esterification catalyst shown in Tables 7 and 8 was added, and the reaction was carried out at 8.0 kPa until the softening points shown in Tables 7 and 8 were reached, obtaining crystalline polyester resins (resins C1 to C11). The physical properties are shown in Tables 7 and 8.

[0111] [Table 7]

[0112] [Table 8]

[0113] Examples 1 to 17, 20 to 25, Comparative Examples 1 to 4 [Melt kneading method] 100 parts by mass of the binder resin shown in Table 9, 5 parts by mass of a colorant "ECB-301" (manufactured by Dainichi Seikagaku Kogyo Co., Ltd., Phthalocyanine Blue (PB15:3)), 3 parts by mass of a release agent "Carnauba Wax C1" (manufactured by Kato Yoko Co., Ltd., melting point: 83°C), and 0.5 parts by mass of a negatively charged charge control agent "Bontron E-304" (manufactured by Orient Chemical Industries Co., Ltd.) were mixed in a Henschel mixer.

[0114] The obtained mixture was melt-kneaded using a co-rotating twin screw extruder with a kneading section total length of 1560 mm, a screw diameter of 42 mm, and a barrel inner diameter of 43 mm at a screw rotation speed of 200 r / min and a barrel set temperature of 100° C. to obtain a melt-kneaded product. The mixture was fed at a rate of 20 kg / h and the average residence time was about 18 seconds.

[0115] The resulting molten mixture was cooled, coarsely crushed, and then crushed in a jet mill. The mixture was classified using an air classifier (manufactured by Nippon Pneumatic Mfg. Co., Ltd.) to obtain the volume median particle size (D 50 ) yielded 7.0 μm toner particles.

[0116] 100 parts by mass of the obtained toner particles were mixed with 1.0 part by mass of hydrophobic silica "R972" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) and 1.0 part by mass of hydrophobic silica "RY-50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) as external additives in a Henschel mixer (manufactured by Nippon Coke and Kogyo Co., Ltd.) at a rotation speed of 3000 r / min (circumferential speed: 32 m / sec) for 3 minutes to obtain a toner.

[0117] Example 18 A toner was obtained in the same manner as in Example 1, except that the melt-kneading was performed using a continuous open-roll type twin-screw kneader "Kneedex" (manufactured by Nippon Coke & Engineering Co., Ltd.) instead of the same-rotation twin-screw extruder. The continuous open-roll type twin-screw kneader had a roll outer diameter of 0.14 m and an effective roll length of 0.8 m, and the operating conditions were a rotation speed of the high-rotation roll (front roll) of 75 r / min (circumferential speed 33 m / min), a rotation speed of the low-rotation roll (rear roll) of 50 r / min (circumferential speed 22 m / min), and a roll gap of 0.1 mm. The heating and cooling medium temperatures in the rolls were set as follows: the temperature of the raw material input side of the high-rotation roll was set to 140°C, and the temperature of the kneaded material discharge side was set to 110°C, and the temperature of the raw material input side of the low-rotation roll was set to 65°C, and the temperature of the kneaded material discharge side was set to 30°C. The supply speed of the raw material mixture was 10 kg / h, and the average residence time was about 5 minutes.

[0118] Example 19 [Emulsion aggregation method] <Preparation of Core Resin Dispersion> 600g of methyl ethyl ketone was put into a 5-liter container equipped with a stirrer, reflux condenser, dropping funnel, thermometer and nitrogen inlet tube, and 129g of resin AH1 and 21g of resin C1 were added at 60°C and dissolved. 5% by mass of sodium hydroxide aqueous solution was added to the obtained solution so that the degree of neutralization was 60 mol% with respect to the acid value of the resin, and the mixture was stirred for 30 minutes to obtain a mixture. Then, 675g of deionized water was added over 77 minutes. Next, while stirring at 250r / min, methyl ethyl ketone was distilled off at a temperature of 50°C or less under reduced pressure, and the solid content concentration of the aqueous dispersion was measured, and the solid content concentration of the aqueous dispersion was adjusted to 20% by mass with deionized water to obtain a core resin dispersion. The volume median particle size (D 50 ) was 200 nm and the CV value was 24%.

[0119] <Preparation of Shell Resin Dispersion> 600g of methyl ethyl ketone was placed in a 5-liter container equipped with a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet tube, and 150g of resin AL1 was added at 60°C and dissolved. A 5% by mass aqueous solution of sodium hydroxide was added to the obtained solution so that the degree of neutralization was 60 mol% relative to the acid value of the resin, and the mixture was stirred for 30 minutes to obtain a mixture. Subsequently, 675g of deionized water was added over 77 minutes. Next, while stirring at 250 r / min, methyl ethyl ketone and a part of the water were distilled off at a temperature of 50°C or less under reduced pressure, and the solid content concentration of the aqueous dispersion was measured, and the solid content concentration of the aqueous dispersion was adjusted to 20% by mass with deionized water to obtain a shell resin dispersion. The volume median particle size (D 50 ) was 110 nm and the CV value was 20%.

[0120] <Preparation of Colorant Dispersion> In a 1-liter beaker, 116.2 g of colorant "ECB-301" (Dainichiseika Color & Chemicals Mfg. Co., Ltd., Phthalocyanine Blue (PB15:3)), 154.9 g of anionic surfactant "Neopelex (registered trademark) G-15" (Kao Corporation, 15% by mass aqueous solution of sodium dodecylbenzenesulfonate) and 260 g of deionized water were mixed and dispersed at room temperature for 3 hours using a homogenizer, and then deionized water was added so that the solids concentration became 24% by mass, thereby obtaining a colorant dispersion. The volume median particle diameter (D 50 ) was 118 nm and the CV value was 27%.

[0121] <Preparation of release agent dispersion> 50 g of Fischer-Tropsch wax (manufactured by Nippon Seiro Co., Ltd., trade name: FNP0090, melting point: 90°C), 5 g of a cationic surfactant (manufactured by Kao Corporation, trade name: Sanisol B50) and 200 g of deionized water were heated to 95°C, and the wax was dispersed using a homogenizer, followed by a dispersion treatment using a pressure discharge homogenizer to obtain a release agent dispersion liquid with a solid content concentration of 20 mass%. The volume median particle diameter (D 50 ) was 550 nm and the CV value was 26%.

[0122] <Preparation of Toner Particles> In a 3-liter four-neck flask equipped with a dehydration tube, a stirrer, and a thermocouple, 500 g of the core resin dispersion, 36 g of the colorant dispersion, 33 g of the release agent dispersion, and 3.3 g of a 15% by mass aqueous solution of sodium dodecylbenzenesulfonate "Neopelex G-15" (manufactured by Kao Corporation, an anionic surfactant) were mixed at a temperature of 25° C. Next, while stirring the resulting mixture, a solution obtained by dissolving 40 g of ammonium sulfate in 570 g of deionized water and adding a 4.8% by mass aqueous solution of potassium hydroxide to adjust the pH to 8.2 was dropped over 10 minutes at 25° C., and the temperature was then raised to 62° C. over 2 hours to measure the volume median particle diameter (D 50 The temperature was maintained at 62° C. until the particle size reached 6.9 μm, thereby obtaining a dispersion of aggregated particles (I).

[0123] While maintaining the temperature of the obtained dispersion of aggregated particles (I) at 62° C., 215 g of the shell resin dispersion was added dropwise at a rate of 0.6 mL / min (0.6 g / min) to obtain a dispersion of aggregated particles (II). 50 ) was 7.0 μm.

[0124] To the dispersion of the obtained aggregated particles (II), an aqueous solution of 20 g of sodium polyoxyethylene lauryl ether sulfate "EMAL E-27C" (Kao Corporation, anionic surfactant, effective concentration 27% by mass), 280 g of deionized water, and 40 g of 0.1 mol / L aqueous sulfuric acid solution was added. The temperature was then raised to 80°C over 1 hour, and the mixture was kept at 80°C for 30 minutes, after which 10 g of 0.1 mol / L aqueous sulfuric acid solution was added and the mixture was kept at 80°C for another 15 minutes. Thereafter, 15 g of 0.1 mol / L aqueous sulfuric acid solution was added again, and the mixture was kept at 80°C until the circularity reached 0.970, thereby obtaining a dispersion of fused particles (core-shell particles) in which the aggregated particles were fused.

[0125] The obtained core-shell particle dispersion was cooled to 30°C, and the dispersion was filtered under suction to separate the solid content, which was then washed with deionized water at 25°C and filtered under suction for 2 hours at 25°C. The solid content was then vacuum dried at 33°C for 24 hours using a vacuum constant temperature dryer "DRV622DA" (manufactured by ADVANTEC) to obtain toner particles. The particle size of the obtained toner particles was 7.0 μm and the circularity was 0.970. The composition ratio (mass ratio) of the binder resin of the obtained toner particles was resin AH1 / resin AL1 / resin C1 = 60 / 30 / 10.

[0126] 100 parts by mass of the obtained toner particles were mixed with 1.0 part by mass of hydrophobic silica "R972" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) and 1.0 part by mass of hydrophobic silica "RY-50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) as external additives in a Henschel mixer (manufactured by Nippon Coke and Kogyo Co., Ltd.) at a rotation speed of 3000 r / min (circumferential speed: 32 m / sec) for 3 minutes to obtain a toner.

[0127] Test Example 1 [Charging Stability of Toner] Under conditions of a temperature of 25°C and a relative humidity of 50%, 0.6 g of toner and 19.4 g of silicone ferrite carrier (manufactured by Kanto Denka Kogyo Co., Ltd., average particle size 90 μm) were placed in a 50 mL polyethylene container and mixed using a ball mill at 250 r / min. The charge amount of the toner was measured using a Q / M meter (manufactured by EPPING Co., Ltd.) using the following method.

[0128] After 60 or 600 seconds of mixing, a specified amount of toner and carrier mixture was put into a cell attached to the Q / M meter, and only the toner was sucked through a 32 μm mesh sieve (stainless steel, twill weave, wire diameter: 0.0035 mm) for 90 seconds. The voltage change on the carrier that occurred at that time was monitored, and the value of [total amount of electricity after 90 seconds (μC) / amount of sucked toner (g)] was taken as the charge amount (μC / g). The ratio of the charge amount after 60 seconds of mixing to the charge amount after 600 seconds of mixing (charge amount after 60 seconds of mixing / charge amount after 600 seconds of mixing) was calculated to evaluate the charge stability. The results are shown in Table 9. The larger the value, the better the charge stability.

[0129] Test Example 2 [Pressure Storage Properties of Toner] 10 g of toner was placed in a cylindrical container with a radius of 12 mm, a weight of 100 g was placed on top, and the toner was stored under pressure for 24 hours in an environment of 50°C and relative humidity of 60%. Three sieves, sieve A (mesh size 250 μm), sieve B (mesh size 150 μm), and sieve C (mesh size 75 μm), were placed on top of each other in a powder tester (manufactured by Hosokawa Micron Co., Ltd.), and 10 g of the toner stored under pressure was placed on sieve A and vibrated for 60 seconds. The weight of the toner remaining on sieve A, WA (g), the weight of the toner remaining on sieve B, WB (g), and the weight of the toner remaining on sieve C, WC (g), were measured, and the pressurized storage stability was evaluated according to the following evaluation criteria based on the value (α) calculated according to the following formula. The results are shown in Table 9. The closer the value (α) is to 100, the better the pressurized storage stability is. α=100-(WA+WB×0.6+WC×0.2) / 10×100

[0130] [Table 9]

[0131] From the above results, it is apparent that in Examples 1 to 25, both the charge stability and pressurized storage stability are good. In contrast, the toners of Comparative Examples 1 and 2, which contain an amorphous polyester resin without using PET, are insufficient in both charge stability and pressurized storage stability, and Comparative Example 2 in particular shows that the use of PET is important, since the use of ethylene glycol and terephthalic acid, which are monomer components of PET, is ineffective. As for the crystalline polyester resin, Comparative Example 3, which does not use ethylene glycol, shows a significant decrease in pressurized storage stability, and Comparative Example 4, which does not use a monofunctional monomer, shows a significant decrease in charge stability. [Industrial Applicability]

[0132] The toner for developing electrostatic images of the present invention is suitably used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like.

Claims

1. A toner for developing electrostatic images, comprising a crystalline polyester resin C and an amorphous polyester resin A, wherein the crystalline polyester resin C is a polycondensate of an alcohol component containing 70 mol % or more of ethylene glycol and a carboxylic acid component containing an aliphatic dicarboxylic acid compound, the alcohol component and / or the carboxylic acid component containing a monofunctional monomer, and the amorphous polyester resin A is a polycondensate of an alcohol component, a carboxylic acid component, and polyethylene terephthalate.

2. 2. The toner for developing electrostatic images according to claim 1, wherein the content of polyethylene terephthalate in the amorphous polyester resin A is 5 mol % or more and 75 mol % or less of the total amount of the alcohol component, the carboxylic acid component and the polyethylene terephthalate, assuming that a terephthalic acid-ethylene glycol unit is 1 mol.

3. 2. The toner for developing electrostatic images according to claim 1, wherein the content of polyethylene terephthalate in the amorphous polyester resin A is 15 mol % or more and 65 mol % or less in the total amount of the alcohol component, the carboxylic acid component and the polyethylene terephthalate, assuming that a terephthalic acid-ethylene glycol unit is 1 mol.

4. 4. The toner for developing electrostatic images according to claim 1, wherein the IV value of the polyethylene terephthalate is 0.40 or more and 0.80 or less.

5. 4. The toner for developing electrostatic images according to claim 1, wherein the content of the crystalline polyester resin C is from 3% by mass to 30% by mass in the total amount of the crystalline polyester resin C and the amorphous polyester resin A.

6. The toner for developing electrostatic images according to any one of claims 1 to 3, wherein in the crystalline polyester resin C, the monofunctional monomer contains an aliphatic monocarboxylic acid compound having 9 to 24 carbon atoms and / or an aliphatic monoalcohol having 9 to 24 carbon atoms.

7. 4. The toner for developing electrostatic images according to claim 1, wherein the content of the monofunctional monomer in the crystalline polyester resin C is from 2 mol % to 30 mol % in the total amount of the alcohol component and the carboxylic acid component.

8. 4. The toner for developing electrostatic images according to claim 1, wherein in the amorphous polyester resin A, the alcohol component contains an aliphatic diol having 3 or more and 6 or less carbon atoms.

9. 9. The toner for developing electrostatic images according to claim 8, wherein the content of the aliphatic diol having 3 to 6 carbon atoms in the alcohol component is 30 mol % to 100 mol %.

10. 4. The toner for developing electrostatic images according to claim 1, wherein in the crystalline polyester resin C, the aliphatic dicarboxylic acid compound has 10 or more and 16 or less carbon atoms.

11. 4. The toner for developing electrostatic images according to claim 1, wherein the amorphous polyester resin A contains an amorphous resin having a softening point different from that of the amorphous polyester resin A by 10° C. or more.

Citation Information

Patent Citations

  • Binder resin composition for toner

    JP2019066536A

  • Toner binder and toner

    JP2019159315A

  • Toner

    JP2021182032A

  • Binder resin composition for toner

    JP2021189196A

  • Binder resin composition for toner

    JP2023013191A